Reliably optimal PMU placement using disparity evolution-based genetic algorithm - Matsukawa, Yoshiaki; Othman, Mohammad Lutfi; Watanabe, Masayuki; Mitani, Yasunori (Universiti Putra Malaysia Press, 2017)
Phasor Measurement Units (PMUs) are an important component in Wide Area Protection (WAP)- based operations in power systems. It is needed that a certain placement scheme of PMUs is suggested if power system scale gets larger. The optimal placement of PMU in power systems has been considered and formulated in order to reduce the number of installed PMUs while accomplishing a desired level of reliability of observation. Optimal PMU Placement (OPP) problem as the combinatorial optimization problem has been formulated to determine the minimum PMU location in the power system. In this paper, Disparity Evolution-type Genetic Algorithm (DEGA) based on disparity theory of evolution is applied. Genetic Algorithm (GA) is employed for the purpose of comparison with DEGA. The optimization model is solved for IEEE 118 standard bus system. DEGA can find better placement suggestion compared with GA because of the nature of evolution that models the double spiral structure of DNA to hold the diversity of population.